Rewilding crops for climate resilience: economic analysis and de novo domestication strategies - Razzaq, Ali; Wani, Shabir Hussain; Saleem, Fozia; Yu, Min; Zhou, Meixue; Shabala, Sergey (Journal of experimental botany, 2021)
This work analyzes the economic cost of global climate changes on crop productivity and argues for a broader use of wild relatives to improve crop stress resilience lost during domestication. Abstract To match predicted population growth, annual food production should be doubled by 2050. This is not achievable by current agronomical and breeding practices, due to the impact of climate changes and associated abiotic stresses on agricultural production systems. Here, we analyze the impact of global climate trends on crop productivity and show that the overall loss in crop production from climate-driven abiotic stresses may exceed US$170 billion year–1 and represents a major threat to global food security. We also show that abiotic stress tolerance had been present in wild progenitors of modern crops but was lost during their domestication. We argue for a major shift in our paradigm of crop breeding, focusing on climate resilience, and call for a broader use of wild relatives as a major tool in this process. We argue that, while molecular tools are currently in place to harness the potential of climate-resilient genes present in wild relatives, the complex polygenic nature of tolerance traits remains a major bottleneck in this process. Future research efforts should be focused not only on finding appropriate wild relatives but also on development of efficient cell-based high-throughput phenotyping platforms allowing assessment of the in planta operation of key genes.